2020
DOI: 10.1111/bjd.18733
|View full text |Cite
|
Sign up to set email alerts
|

High capillary diameter in psoriatic plaques of the lower legs

Abstract: Linked Article: Hjuler et al. Br J Dermatol 2019; 181:332‐7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…Lacarruba et al stated that there is a higher mean capillary bush diameter in psoriatic plaques located on the lower limbs, reflecting increased vascular flow and thus, delaying the response and resistance to the incriminated therapy, although other factors, including stasis and hydrostatic pressure, may be considered 20 . Further studies are needed to support these findings; if confirmed, then the lower limbs may be included in difficult‐to‐treat areas, along with the nails, palmo‐plantar, genital, scalp, and intertriginous areas.…”
Section: Discussionmentioning
confidence: 99%
“…Lacarruba et al stated that there is a higher mean capillary bush diameter in psoriatic plaques located on the lower limbs, reflecting increased vascular flow and thus, delaying the response and resistance to the incriminated therapy, although other factors, including stasis and hydrostatic pressure, may be considered 20 . Further studies are needed to support these findings; if confirmed, then the lower limbs may be included in difficult‐to‐treat areas, along with the nails, palmo‐plantar, genital, scalp, and intertriginous areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been hypothesized that the inflammation leads to an increased tendency for edema, so that the healing of the inflammatory reaction is slowed by stasis. 13 The support of psoriasis healing by compression therapy has only been described casuistically. A patient with psoriasis on both extensor surfaces of the knees was fitted with a compressive knee brace for osteoarthritis.…”
Section: Compression Therapy For Inflammatory Dermatosesmentioning
confidence: 99%
“…The precise reason behind the impaired healing of psoriasis plaques on the lower legs is not yet fully understood. However, it has been hypothesized that the inflammation leads to an increased tendency for edema, so that the healing of the inflammatory reaction is slowed by stasis 13 . The support of psoriasis healing by compression therapy has only been described casuistically.…”
Section: Indications For Compression Therapymentioning
confidence: 99%
“…Diskutiert wird, dass es durch die Inflammation zu einer vermehrten Ödemneigung kommt, sodass die Abheilung der Entzündungsreaktion stasebedingt verlangsamt abläuft. 13 Die Unterstützung der Abheilung bei Psoriasis durch Kompressionstherapie wurde bislang lediglich kasuistisch beschrieben. Bei einer Psoriasis an beiden Streckseiten der Knie wurde aufgrund einer Osteoarthritis eine kompressive Kniebandage getragen.…”
Section: Kompressionstherapie Entzündlicher Dermatosenunclassified
“…Warum Psoriasis‐Plaques an den Unterschenkeln nur erschwert abheilen, ist nicht genau bekannt. Diskutiert wird, dass es durch die Inflammation zu einer vermehrten Ödemneigung kommt, sodass die Abheilung der Entzündungsreaktion stasebedingt verlangsamt abläuft 13 . Die Unterstützung der Abheilung bei Psoriasis durch Kompressionstherapie wurde bislang lediglich kasuistisch beschrieben.…”
Section: Indikationen Der Kompressionstherapieunclassified